Between urban and rural: towards an understanding of metropolitan edge - López Goyburu, Patricia Lucia (2024)
The need to act on urban expansion has been a common concern throughout the history of urbanism. Different authors have shown how in industrialized countries the olddistinctions between urban and rural become blurred. The location and conformationof new leisure, commercial and tertiary objects have become triggers for new looksat the urbanization edges of industrial cities. Although they have been less exploredin non-industrial cities or cities with a lower degree of industrialization, different studies show that these characteristics seem to be combined there with other factors suchas social housing, progressive expansion of the urban fabric and degraded areas. Nevertheless, could there be a theory that enlightens the conditions and transformationsof the metropolitan edge and guides their research? The aim of this work is to comparefour key approaches: spaces in socio-spatial transformation, multi-actor project, multiple, dynamic and heterogeneous uses, and non-universal spatial delimitation, focusingon three categories: concept, attribute, and methodology. This research is groundedin the selection of relevant publications based on their substantive scope, significant impact factor index, and/or number of citations, as well as the international recognitionof researchers. These findings underscore the importance of theorizing the metropolitanedge as a process that transforms inherited spaces according to their socio-economic,historical, and environmental contexts. The results reflect the need for denominationsand classifications that help us to differentiate analytically and cartographically the multiple landscapes of the metropolitan edge and question us about the specificity of thisterritory that extends between urban nuclei and rural space, the processes that haveoverlapped over time, and their logics.